Usage Dynamics of Telecenters in São Paulo, Brazil - Spence, Jeremiah (2007)
Building upon the methodology developed and presented in Straubhaar, Ferreira, e Spence (2006), this article presents an introductory analysis of the trends of the user base for the Acessa São Paulo Program (Acessa SP), a digital inclusion initiative of the government of the State of São Paulo (Brazil) that since 2001 has offered free access to the Internet and e-government services through local partnerships. Acessa SP currently, as of November 2006, funds and operates telecenters installed in partnerships with community associations, government-funded organizations and local governments. The Ponline research is an annual survey applied online in all the 392 participating telecenters in the program, which mapped and profiled the frequent users’ habits and attitudes in relation to the new technologies and personal and community impacts. This article provides of a framework for the classification of the telecenters operated by the Acessa SP program, and utilizes an extensive dataset collected through the annual Ponline telecenter user survey, which was presented in November 2006 to the government of the State of São Paulo. Building upon the conceptual framework of the previous work this article will allow for comparative analysis between the telecenters of the Acessa SP network and similar national and international projects, as well as, complementary datasets.